Geographically-aware mobile application for managing events and interest group communications - Lee, Chong Yan (Nanyang Technological University, 2021)
Crowdsourcing has become increasingly prevalent [1] as people source for more information and services from one and another over social media platform. The proliferation of social media platforms, such as Instagram, Facebook, Twitter and Reddit, is attributed to humans’ need for more information to make more informed decision or to simply get together to fish out common gossips within the communities, with the likes of Reddit and Twitter.